2017
DOI: 10.1007/s13224-017-1025-0
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status and Fertility Treatment Including IVF

Abstract: Oral health is extremely important for the general wellbeing of the individual. From a number of research articles, it is established that there is a definitive connection between periodontal health and many systemic diseases, like type II diabetes, cardiovascular diseases and even preterm labor and low birth weight of babies. The significant rate of failure in the treatment of infertility and IVF (in vitro fertilization) even with multiple advancements in the last decade has made scientist take interest in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Human studies indicate that many body systems are affected by the presence of periodontal disease. 17,18,19 Donkey studies have shown links between dental disease and weight loss, colic and low body condition. 20,21 Extraction of teeth affected with severe periodontal disease may lead to exacerbation of malocclusions due to supereruption of unopposed cheek teeth, or spread of periodontal disease within the oral cavity due to drift of the teeth remaining in the row and secondary diastema formation.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies indicate that many body systems are affected by the presence of periodontal disease. 17,18,19 Donkey studies have shown links between dental disease and weight loss, colic and low body condition. 20,21 Extraction of teeth affected with severe periodontal disease may lead to exacerbation of malocclusions due to supereruption of unopposed cheek teeth, or spread of periodontal disease within the oral cavity due to drift of the teeth remaining in the row and secondary diastema formation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the maternal periodontal health has widespread effects on the developing foetus and recent researches have also found a relationship between the expectant mother's periodontal condition and her fertility status [12]. These revelations indicate an intricate relationship between the hormonal infertility drugs and the periodontal /gingival status of the woman that must be explored in more depth [13].…”
Section: Introductionmentioning
confidence: 99%
“…considerable (Khalife & Khalil, 2019); this has prompted the scientific community to focus its attention on other health parameters, including the influence of the maternal periodontal status on the success of fertility treatments. Although there are not many studies on this topic, from a study conducted by Khanna et al in 2017, it has been highlighted a correlation between the gingival index before treatment and the number of oocytes obtained following ovarian stimulation and between the number of embryos suitable for the implant and the gingival index after in vitro fertilization. Moreover, the study underlined a link between the maternal periodontium, the administration of hormonal therapy before treatment and its influence on the outcome of the therapy.…”
mentioning
confidence: 99%
“…Moreover, the study underlined a link between the maternal periodontium, the administration of hormonal therapy before treatment and its influence on the outcome of the therapy. Therefore, it could be inferred that the maternal periodontium can be affected by the hormonal therapies administered before the execution of in vitro fertilization and that this may affect the effectiveness of the treatment (Khanna, Dhaimade, & Malhotra, 2017). However, in 2019 Dhalia Kalife and colleagues questioned that the presence of periodontitis may represent a risk factor for the positive outcome of an infertility treatment, and no apparent link was found between pre-existing periodontal disease and adverse outcomes of in vitro fertilization.…”
mentioning
confidence: 99%